Mycosubtilin Produced by Bacillus subtilis ATCC6633 Inhibits Growth and Mycotoxin Biosynthesis of Fusarium graminearum and Fusarium verticillioides - Chenjie Yu (MDPI AG, 2021)
Fusarium graminearum and Fusarium verticillioides are fungal pathogens that cause diseases in cereal crops, such as Fusarium head blight (FHB), seedling blight, and stalk rot. They also produce a variety of mycotoxins that reduce crop yields and threaten human and animal health. Several strategies for controlling these diseases have been developed. However, due to a lack of resistant cultivars and the hazards of chemical fungicides, efforts are now focused on the biocontrol of plant diseases, which is a more sustainable and environmentally friendly approach. In the present study, the lipopeptide mycosubtilin purified from Bacillus subtilis ATCC6633 significantly suppressed the growth of F. graminearum PH-1 and F. verticillioides 7600 in vitro. Mycosubtilin caused the destruction and deformation of plasma membranes and cell walls in F. graminearum hyphae. Additionally, mycosubtilin inhibited conidial spore formation and germination of both fungi in a dose-dependent manner. In planta experiments demonstrated the ability of mycosubtilin to control the adverse effects caused by F. graminearum and F. verticillioides on wheat heads and maize kernels, respectively. Mycosubtilin significantly decreased the production of deoxynivalenol (DON) and B-series fumonisins (FB1, FB2 and FB3) in infected grains, with inhibition rates of 48.92, 48.48, 52.42, and 59.44%, respectively. The qRT-PCR analysis showed that mycosubtilin significantly downregulated genes involved in mycotoxin biosynthesis. In conclusion, mycosubtilin produced by B. subtilis ATCC6633 was shown to have potential as a biological agent to control plant diseases and Fusarium toxin contamination caused by F. graminearum and F. verticillioides.